Disrupted endoplasmic reticulum-mediated autophagosomal biogenesis in a Drosophila model of C9-ALS-FTD. - Sung, H.; Lloyd, T.E. (Autophagy, 2024)
Macroautophagy/autophagy is a major pathway for the clearance of protein aggregates and damaged organelles, and multiple intracellular organelles participate in the process of autophagy, from autophagosome formation to maturation and degradation. Dysregulation of the autophagy pathway has been implicated in the pathogenesis of neurodegenerative diseases including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), however the mechanisms underlying autophagy impairment in these diseases are incompletely understood. Since the expansion of GGGGCC (G4C2) repeats in the first intron of the C9orf72 gene is the most common inherited cause of both ALS and FTD (C9-ALS-FTD), we investigated autophagosome dynamics in Drosophila motor neurons expressing 30?G4C2 repeats (30?R). In vivo imaging demonstrates that expression of expanded G4C2 repeats markedly impairs biogenesis of autophagosomes at synaptic termini, whereas trafficking and maturation of axonal autophagosomes are unaffected. Motor neurons expressing 30?R display marked disruption in endoplasmic reticulum (ER) structure and dynamics in the soma, axons, and synapses. Disruption of ER morphology with mutations in Rtnl1 (Reticulon-like 1) or atl (atlastin) also impairs autophagosome formation in motor neurons, suggesting that ER integrity is critical for autophagosome formation. Furthermore, live imaging demonstrates that autophagosomes are generated from dynamic ER tubules at synaptic boutons, and this process fails to occur in a C9-ALS-FTD model. Together, these findings suggest that dynamic ER tubules are required for formation of autophagosomes at the neuromuscular junction, and that this process is disrupted by expanded G4C2 repeats that cause ALS-FTD.